Quality and Sensory Evaluation of Meat of Ducks (Cairina moschata) in Confinement under Different Nutritional Plans and Housing Densities - Rufino, Joao Paulo Ferreira; Cruz , Frank George Guimaraes; Melo, Lucas Duque; Soares, Verena Makarem; Curcio, Uriel de Almeida; Damasceno, Jessica Lima; Costa, Ana Paula Guimaraes Cruz (International Journal of Poultry Science, 2014)
The objective of this study was to evaluate the quality of meat ducks are raised in confinement under different phasic nutritional plans in different housing densities. Were used 240 ducks (Cairina Moschara) creoles of mixed batches housed in experimental shed with water and food ad libitum. The experimental design was completely randomized in a factorial arrangement 3 x 2, with three feeding plans and two housing densities. The plans were: P1 with 3 phases (1-35, 36-70 and 71-90 days), P2 with 4 phases (1-28, 29-49, 50-72 and 73-90 days) and P3 with 5 phases (1-14, 14-28, 29-63, 64-76 and 77-90 days) and housing densities (2 and 3 birds/m2) with 4 repetitions totaling 24 experimental units. Were slaughtered at 90 days of age 2 birds from each plot for measuring the quality of post-slaughter meat and sensory analysis. Significant differences were found for weight wing (p0.05) among population densities, with the nutritional plan with three phases and the density of 2 birds/m2 showing better results. Wasn’t found any significant differences for physical measurements of chest and leg and sensory analysis of meat (p>0.05). Significant differences for pH chest and leg were found, with better results for extended nutritional plans and density of 2 birds/m2. Nutritional plans with reduced phases and lower housing densities have better results for development and meat quality of commercial cuts of creole ducks. Future studies are necessary to determine the influence of other nutritional requirements in meat ducks are raised in confinement.